Ketahanan Keuangan Provinsi Jawa Barat Selama Pandemi (Studi Pada 27 Kabupaten/Kota di Provinsi Jawa Barat) - Hans Victor Sitepu; Mirza Melia Amatunnisaa; Janah; Baitiya Mu'minan; Misbahhudin (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
Covid-19 has had a great global influence, notably in Indonesia. West Java, Indonesia's most populous province, is expected to pursue economic recovery policies throughout the epidemic, albeit this has not been practically proven. This study sought to determine whether there were substantial disparities in the financial performance of 27 regencies/municipalities in West Java Province before and throughout the pandemic over a two-year period (2018–2021). Mathematical computations, descriptive statistics, and inferential analysis using paired t-test calculations for each average financial performance metric were used. Despite the difficult conditions during the pandemic, this study reveals that numerous regencies/municipalities in the West Java Province region had positive financial outcomes. Ten regencies/ municipalities saw a rise in fiscal decentralization, effectiveness ratio, and efficiency ratio. Aside from that, 8 districts/cities gained independence throughout the epidemic. Not to mention that six regencies/cities showed increased growth rates during the outbreak.